P30 Early outcomes in adults with palliated hypoplastic left heart syndrome. (2nd March 2016) - Ooues, G; Arif, S; Bowater, S; Thorne, S; Hudsmith, L; Clift, P
Abstract : Background: Patients with palliated hypoplastic left heart syndrome (HLHS) are now surviving into adulthood. We anticipate that these patients may develop significant morbidity related to their Fontan circulation. We sought to determine long-term complications including cardiac symptoms, structural pathology, such as ventricular failure, atrio-ventricular valve regurgitation, and rhythm disturbances. Methods: We performed a retrospective review of the case notes of all patients with HLHS under our care, reviewing clinic letters, cardiac imaging and exercise tests. Results: We identified 27 HLHS patients (75% male) with mean age 20.4 ± 2.9 years. The majority of patients (74%) had undergone a stage III (Fontan) definitive palliation. At their last clinic review, only 37% (n = 10) of patients were breathless on exertion of which 6 had NYHA III symptoms. Mean arterial saturations were 90% (range of 71–97%) and mean peak oxygen consumption (VO2 max) was 25.3 ml/kg/min (mean 60% predicted). 70% of patients (n = 19) had evidence of systemic right ventricular impairment ranging from mild (n = 12, 44%) to severe (n = 2, 7%). 74% (n = 20) had evidence of mild or moderate systemic atrio-ventricular valve regurgitation. No patients developed significant heart failure requiring advanced therapy or cardiac transplantation. All patients were in sinus rhythm, 30% (n = 8) had previous rhythm disorders; 3 atrial flutter requiring electrical or medical cardioversion and ablations, 1 non-sustained ventricular tachycardia and 4 bradyarrhythmias requiring permanent pacemaker insertion. 89% (n = 24) of patients were anti-coagulated with Warfarin. 1 patient suffered an ischaemic stroke. No other complications of Fontan circulation, such as hepatic dysfunction or protein losing enteropathy, were seen. Conclusion: We describe our experience of HLHS patients following transition to adult care. In general, HLHS patients reach early adulthood without any significant complications. The majority have a mild degree of systemic ventricular impairment. Rhythm disturbances are, so far, rare. Ongoing longitudinal follow up is necessary to establish the long term consequences of Fontan palliation for HLHS.